2016
DOI: 10.1294/jes.27.169
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the bispectral index as an indicator of anesthetic depth in Thoroughbred horses anesthetized with sevoflurane

Abstract: To evaluate the bispectral index (BIS) as an indicator of anesthetic depth in Thoroughbred horses, BIS values were measured at multiple stages of sevoflurane anesthesia in five horses anesthetized with guaifenesin and thiopental following premedication with xylazine. There was no significant difference between the BIS values recorded at end-tidal sevoflurane concentrations of 2.8% (median 60 ranging from 47 to 68) and 3.5% (median 71 ranging from 49 to 82) in anesthetized horses. These BIS values during anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…BIS monitoring is useful for measuring anesthesia depth during veterinary surgery 14,21–24 and has been applied to dogs, 14,22–26 calves, 27,28 horses, 29,30 rabbits, 31,32 pigs, 33–35 and other animals housed in zoos 36 . The preferred BIS values for anesthetized dogs, rabbits, and horses range from 40 to 60, 21 52 to 61, 32 and 47 to 68, 30 respectively. To ensure strong brainwave signals, SIQ and EMG values should be >50 and <40, respectively 21 .…”
Section: Discussionmentioning
confidence: 99%
“…BIS monitoring is useful for measuring anesthesia depth during veterinary surgery 14,21–24 and has been applied to dogs, 14,22–26 calves, 27,28 horses, 29,30 rabbits, 31,32 pigs, 33–35 and other animals housed in zoos 36 . The preferred BIS values for anesthetized dogs, rabbits, and horses range from 40 to 60, 21 52 to 61, 32 and 47 to 68, 30 respectively. To ensure strong brainwave signals, SIQ and EMG values should be >50 and <40, respectively 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiment using isoflurane ( 21 ), propofol ( 22 ), sevoflurane, or halothane ( 23 ) showed the poor quality of BIS to accurately anticipate movements during surgery in horses. Nevertheless, a recent study demonstrated that the BIS value could be useful as an indicator of awakening during the recovery period in horses ( 24 ). In our study, BIS values did not allow to anticipate episodes of awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of their changes depends on the stimulation of the autonomic nervous system and is partially related to the intensity of nociceptive signals. Therefore, it seems reasonable to introduce an EEG measurement due to its high specificity and sensitivity (limited number of wave patterns and a large number of variables affecting them) to show the changes of the level of consciousness, which in combination with cardiopulmonary parameters will enable accurate assessment of the patient's clinical condition during general anesthesia [40].…”
Section: Eeg Monitoring During General Anesthesia: Does It Improve Anmentioning
confidence: 99%
“…Such library (collected measurements of EEG specific for different levels of anesthesia depth) was created only for people so far, and the adequacy of results obtained by algorithms to the clinical state of patient was proved. In the case of horses, research has been conducted on the bispectral index (BI) algorithm [40,41], Narcotrend [42] and patient state index (PSI). Up to now, they were not confirmed to be accurate because of the differences in the activity of waves in humans and horses, and thus the lack of usefulness of human EEG records used for algorithms in horses only serves as study guidelines.…”
Section: Analysis Of Eeg and Its Usefulness In Equine General Anesthesiamentioning
confidence: 99%